Cartoon - "Not our sort of unity", 1930s
1939 1918-1939 "Cartoon - "Not our sort of unity", 1930s" [T0460.jpg], 1930s This anti - fascist cartoon ridiculing the Blackshirts of the New Party, founded by Oswald Mosley, is from the General and Municipal Workers Union Journal for October 1933.